Genomes of 211 Actinomycete Strains from Diverse Environments - Yue Liu; Zhengjiao Liang; Jingya Shi; Xiaonan Lin; Puzi Jiang; Haoyuan Sun; Fengling Chen; Zhen Yue; Xiaodong Fang; Yonghua Hu; Haixin Chen (Scientific Data)
Abstract Actinomycetes are a highly diverse group of microorganisms that have long been recognized as a valuable source of antibiotics and other bioactive metabolites. Recent advances in genome mining have revealed a wealth of previously unexplored silent secondary metabolite biosynthetic gene clusters (smBGCs) in actinomycete genomes, underscoring their untapped bioactivity potential. Here, we present the genome sequences of 211 actinomycete strains isolated from various environmental sources, generated through high-throughput sequencing. The resulting genome assemblies exhibit high completeness and accuracy, offering high-quality data for downstream analyses and biological resource exploration.